The Risk of Tuberculosis Transmission in Solid Organ Transplant: Is It More Than a Theoretical Concern?. Issue 5 (2005) - Rose, Gregory
Abstract : The present case report describes a therapeutic dilemma regarding the transmission of Mycobacterium tuberculosis during transplantation of solid organs, places this phenomenon within the context of the literature, and makes recommendations for screening and therapy.